1989
DOI: 10.1177/009102608901800409
|View full text |Cite
|
Sign up to set email alerts
|

Major Unions and Collectively Bargained Fringe Benefits

Abstract: Fringe benefits are a growing part of the compensation package. Unions and employee associations have played a significant role in the development of fringe benefits. A survey of major unions and employee associations indicates of the new fringe benefits dental coverage, vision coverage, employee assistance programs, maternity leave, and alternative work schedules are the most prevalent in current contracts. Sabbatical leaves are most prevalent as a new benefit in current negotiations, and child care, eldercar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Besides, the Trade Union coordinates with a firm to build collective bargaining agreements and internal labor regulations. This means that unions are involved in formulating strategies on working hours, occupational safety, insurance, and health care [62][63][64][65]. Therefore, the existence of trade unions in enterprises can improve working conditions.…”
Section: The Effect Of Export Participation On Working Conditionsmentioning
confidence: 99%
“…Besides, the Trade Union coordinates with a firm to build collective bargaining agreements and internal labor regulations. This means that unions are involved in formulating strategies on working hours, occupational safety, insurance, and health care [62][63][64][65]. Therefore, the existence of trade unions in enterprises can improve working conditions.…”
Section: The Effect Of Export Participation On Working Conditionsmentioning
confidence: 99%
“…15 (Kemp, 1989) 16 (Doheny, 1999) 17 (Dougherty, 2010) Practical Implications for Employees The health reform bill passed by Congress in March 2010 defined a high-cost (Cadillac) health plan based on the size of the premium. If a premium costs more than $10,200 for an individual or $27,500 for a family, insurers are subject to a 40% tax of the amount of the premium that exceeds these levels.…”
Section: The Structure and Composition Of Employee Benefitsmentioning
confidence: 99%
“…Third, research has found that drug testing is more prevalent in transportation and manufacturing settings where risks of drug-related accidents and injuries are perceived to be greater (Gomez-Mejia and Balkin, 1987;Masters, Ferris and Ratcliff, 1988;Mellow, 1988). Fourth, it has been shown (Kemp, 1989) that unions are actively involved in negotiating for employee assistance programs. In the case of the various types of drug testing, the role of unions varies.…”
Section: Control Variablesmentioning
confidence: 99%